2001
DOI: 10.1212/wnl.56.12.1666
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of stroke in rat with intracarotid administration of marrow stromal cells

Abstract: MSC injected intra-arterially are localized and directed to the territory of the middle cerebral artery, and these cells foster functional improvement after cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
261
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(281 citation statements)
references
References 46 publications
(35 reference statements)
14
261
0
4
Order By: Relevance
“…We also found on day 14 that the MSC-only treated group could significantly reduce the infarction volume under the superacute treatment compared with the PBS-treated group, but not under the acute treatment. This was the same as the Chopp's group had reported, that transplanted MSCs to the transient MCAO model 24 h after ischemia occurred had improved neurological function recovery, but not significantly decreased infarction area Li et al, 2000Li et al, , 2001, while our data of the superacute treatment showed the contrast result. We thought that it might have been caused by the different therapeutic time window.…”
Section: Discussionsupporting
confidence: 89%
“…We also found on day 14 that the MSC-only treated group could significantly reduce the infarction volume under the superacute treatment compared with the PBS-treated group, but not under the acute treatment. This was the same as the Chopp's group had reported, that transplanted MSCs to the transient MCAO model 24 h after ischemia occurred had improved neurological function recovery, but not significantly decreased infarction area Li et al, 2000Li et al, , 2001, while our data of the superacute treatment showed the contrast result. We thought that it might have been caused by the different therapeutic time window.…”
Section: Discussionsupporting
confidence: 89%
“…64 Neuroprotective effects were also observed by MSC infusion in animal models of stroke. 65 It is noteworthy that common paracrine mechanisms, independent of transdifferentiation, appear to support MSC therapeutic plasticity for a wide range of experimental diseases.…”
Section: Animal Models Of Tissue Protectionmentioning
confidence: 99%
“…cardiomyocytes [7][8][9], hepatocytes [10,11], and endothelial cells [12]. Especially, a large of body of evidence have indicated that mouse, rat, and human bone marrow MSCs can be induced to differentiate to neuron-like cells in culture [13][14][15][16] and further verified by the transplantation experiments in animal models of Parkinson's disease [17], stroke [18,19], cerebral ischemia [20], spinal cord injury [21], and Niemann-Pick disease [22]. However, despite many transplantation studies showing beneficial effects, most studies report low levels of cell persistence and neuronal differentiation in vivo.…”
Section: Introductionmentioning
confidence: 99%